RELATIONSHIP OF WASTE MANAGEMENT WITH KNOWLEDGE, ATTITUDE AND PARTICIPATION OF TRADERS IN THE TRADITIONAL EGGPLANT MARKET IN MAKASSAR - Syahril Idris; Nurlita Pertiwi; Syamfitriani Asnur; Syamsuddin Mustafa (International Conference on Social and Islamic Studies, 2021)
Eggplant Traditional Market is one of the traditional markets located in the center of Makassar City. This traditional market is every day a busy market visited by the community, because this market sells various types of merchandise, so this traditional market produces waste every day. This study aims to determine by describing and analyzing the relationship between knowledge, attitudes and availability of facilities with the participation of traders in waste management at the Eggplant Traditional Market in Makassar City.This research is a descriptive quantitative research to describe, explain, or summarize various conditions, situations, phenomena, or various research variables. The test results from the study are described by tables and the percentage values ​​obtained by the Eggplant Traditional Market in Makassar City.From the results of the research that has been done, it can be concluded that there is a significant relationship between knowledge, attitudes and availability of facilities with the participation of traders in waste management at the Eggplant Traditional Market.